Analisis Kepuasan Konsumen Gojek di Wilayah Kota Palangka Raya - Billy Robertus Vandogi; Sutan Parasian Silitonga; Robby Robby (Sosio e-Kons, 2021)
Online transportation is currently popular among the general public, and one of them is Gojek, Gojek is very interesting to learn how to use it in Palangka Raya City. This research with the theme of consumer satisfaction with Gojek services in the Palangka Raya City area aims to determine the Gojek consumer satisfaction level model in Palangka Raya City. We conducted an online survey of Gojek users and conducted an analysis using the ordinal logit method in Palangka Raya City and it is processed by using the SPSS software so that it can be seen about the things that affect customer satisfaction for motorbikes in Palangka Raya City. The results showed that the model of the level of satisfaction was determined by age, occupation, safety, traffic violations, friendliness, unsuitable payment in the application. And a very significant technical performance is security, so it is recommended that the level of satisfaction really depends on the safety conditions of the Gojek model going forward.